Об одном классе модулей над групповыми кольцами локально разрешимых групп с условием min−nnd - Дашкова, О.Ю. (Доповіді НАН України, 2011)
Досліджено RG-модуль A такий, що R — цілісне кільце, група G локально розв'язна, CG(A)=1, фактормодуль A/CA(G) не є нетеровим R-модулем та система всіх підгруп H≤G, для яких фактормодулі A/CA(H) не є нетеровими R-модулями, задовольняє умову мінімальності. Ця умова називається умовою min−nnd. Отримано деякі властивості групи G. An RG-module A such that R is an integral ring, a group G is locally soluble, CG(A)=1, the quotient module A/CA(G) is not a Noetherian R-module, and the system of all subgroups H≤G for which the quotient modules A/CA(H) are not Noetherian R-modules satisfies the minimal condition on subgroups is studied. This condition is called the condition min−nnd. Some properties of the group G are obtained.